E-2: ENHANCING INNOVATIVE WORK BEHAVIOR IN PAKISTAN'S SOFTWARE INDUSTRY: THE MEDIATING IMPACT OF EMPLOYEE FEEDBACK SEEKING AND PSYCHOLOGICAL EMPOWERMENT ON TRENHANCING INNOANSCENDENTAL LEADERSHIP - Ajmal , Muhammad; Islam, Azmat; Khan, Imran (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2024)
This study investigates the influence of Transcendental Leadership on Innovative Work Behavior (IWB) in the software industry of Pakistan, with a focus on the cities of Lahore, Karachi, and Islamabad. The research explores how Employee Feedback Seeking Behavior (EFSB) and Psychological Empowerment (PE) mediate this relationship. A quantitative research design was employed, involving a survey administered to 350 employees working in various software companies across the mentioned cities. Transcendental Leadership, characterized by vision, altruism, and integrity, is posited as a significant predictor of IWB, an essential component for organizational innovation and competitiveness. The study examines whether EFSB and PE serve as crucial links between Transcendental Leadership and IWB, suggesting that these mediating factors could amplify or attenuate the Leadership's impact on innovation. The findings indicate a positive relationship between Transcendental Leadership and IWB, with both EFSB and PE playing significant mediating roles. Specifically, the results demonstrate that employees who actively seek feedback and feel empowered are more likely to engage in innovative behaviors, particularly when led by a transcendental leader. This highlights the importance of fostering an environment that encourages feedback-seeking and enhances employees' sense of empowerment to cultivate innovation. This research contributes to the literature on Leadership and innovation in the context of Pakistan's burgeoning software industry. It offers insights for practitioners and leaders in the software sector, suggesting that adopting Transcendental Leadership practices could be a strategic approach to enhancing innovation. Furthermore, it emphasizes the need for organizational policies that support feedback-seeking behaviors and psychological empowerment among employees to foster a culture conducive to innovation. By elucidating the mediating roles of EFSB and PE in the relationship between Transcendental Leadership and IWB, this study provides a nuanced understanding of how Leadership can effectively drive innovation in the software industry, with implications for both theory and practice.